The physico-mathematical theory of human erythrocyte hypotonic hemolysis phenomenon - Gordienko, E.A.; Gordienko, Yu.E.; Gordienko, O.I. (c/o Royal Veterinary Colledge, London, 2003)
A physico-mathematical model of human erythrocyte hypotonic hemolysis has been developed in this work. It quantitatively describes the kinetics of the phenomenon occurring when cells are suspended in an hypertonic aqueous solution of permeable non-electrolyte
Keywords: Human erythrocyte; Physico-mathematical model; Hypotonic hemolysis; Cell swelling